A survey of arabic text mining - Salloum, Said A.; AlHamad, Ahmad Qasim; Al-Emran, Mostafa; Shaalan, Khaled (Springer, 2017)
Recently, text mining has become an interesting research field due to the huge amount of existing text on the web. Text mining is an essential field in the context of data mining for discovering interesting patterns in textual data. Examining and extracting of such information patterns from huge datasets is considered as a crucial process. A lot of survey studies were conducted for the purpose of using various text mining methods for unstructured datasets. It has been noticed that comprehensive survey studies in the Arabic context were neglected. This study aims to give a broad review of various studies related to the Arabic text mining with more focus on the Holy Quran, sentiment analysis, and web documents. Furthermore, the synthesis of the research problems and methodologies of the surveyed studies will help the text mining scholars in pursuing their future studies.